Pendidikan Islam Transformatif dalam Menjembatani Diskursus Agama dan Sains untuk Masa Depan Kemanusiaan - Ari Yudhanto Prabowo; Jimmy Malintang; Mahfud Junaedi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research explores the concept of Transformative Islamic Education as a means to bridge the discourse between religion and science, aiming to nurture a generation that is faithful, knowledgeable, and capable of making a positive impact on humanity’s future. Amid globalization and rapid technological advancements, individuals face increasingly complex challenges, highlighting the necessity of integrating spiritual values with scientific understanding. Transformative Islamic Education not only prioritizes academic excellence but also emphasizes character development, moral values, and social awareness. Utilizing a qualitative methodology and literature review, the study investigates principles of Islamic education and practices that integrate religion and science. The findings indicate that holistic education equips students to respond effectively to social and environmental challenges, empowering them to become agents of change within their communities. Consequently, Transformative Islamic Education holds the potential to develop well-rounded individuals with integrity, competitiveness, and a strong commitment to creating a better world, aligning with the Islamic principle of rahmatan lil 'alamin.